ACERCA DE LA MEGAFAUNA DEL CRETACICO SUPERIOR DE HUANTRAICO, PROVINCIA DEL NEUQUEN (ARGENTINA) (Ameghiniana, 2013)
The megafaune of Huantraico, province of Neuquén, is composed by the genus: Ostrea, Gryphea, Gryphaeostrea, Pecten, Lima, Pterotrigonia, Turritella, Baculites, Eubaculites, etc. Ostrea lingua, Pecten modestus, Lima (Limatula) angusta, and Gryphea regionis are new. The age of this faune is Maestrichtian.